PENGARUH KESADARAN WAJIB PAJAK, TINGKAT PENDAPATAN, KUALITAS PELAYANAN DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN - Ratu, Raimundus; Sayang, Sabulon; Reo, Hermanus (Program Studi Akuntansi Universitas Flores, 2024)
This study aims to determine the effect of taxpayer awareness, income level, service quality and tax knowledge on taxpayer compliance in paying land and building tax in Kawalelo Village, Demon Pagong District, East Flores Regency. This research is a type of causality research. The sampling technique uses purposive sampling totaling 100 respondents. The data analysis techniques used are Descriptive Analysis, Data Quality Test, Classical Assumption Test, Multiple Regression Analysis, and Hypothesis Test. The results of this study show that: (1) Taxpayer Awareness affects Taxpayer Compliance in paying Land and Building tax in Kawalelo Village, Demon Pagong District, East Flores Regency, this is evidenced by the test results which show the value of the taxpayer awareness variable coefficient of 0.395 with a calculation of >ttable (3.930 >1.98525) and a significant level of 0.000<0.05. (2) The level of income has a significant effect on taxpayer compliance in paying land and building tax in Kawalelo Village, Demon Pagong District, East Flores Regency, this is evidenced by the test results which show the value of the variable coefficient of income level of 0.294 with a calculation of >ttable (2.454 >1.98525) and a significant level of 0.016 < 0.05 . (3) Service Quality has a significant effect on taxpayer compliance in paying land and building tax in Kawalelo Village, Demon Pagong District, East Flores Regency, this is evidenced by the test results which show the value of the Service Quality variable coefficient of 0.305 with t>tabel(2.418>1.98525) and a significant level of 0.018<0.05. (4) Taxation knowledge has no effect on taxpayer compliance in paying land and building tax in Kawalelo Village, Demon Pagong District, East Flores Regency, this is evidenced by the test results which show the value of the tax knowledge variable coefficient of 0.025 with t<tabel(0.244<1.98525) and a significant level of 0.808 > 0.05. Based on the results of the determinant coefficient test (R2) shows that the percentage of contribution of the influence of independent variables (Taxpayer Awareness, Income Level, Service Quality and Tax Knowledge) on the dependent variable (Taxpayer Compliance in paying Land and Building tax) is 52.4% and the remaining 47.6% is influenced by variables outside the model that are not explained.